Remote Digital Support for Adults with Pulmonary Tuberculosis: A Systematic Review - Yulmira Tisel; Ira Suarilah; Erna Dwi Wahyuni (Universitas Pahlawan Tuanku Tambusai, 2025)
Remote digital health services, including Video Directly Observed Therapy (VDOT) and Wirelessly Observed Therapy (WOT), offer a promising alternative to traditional Directly Observed Therapy (DOT) for tuberculosis (TB) treatment adherence. This systematic review, following PRISMA guidelines, analyzed 10 randomized controlled trials (RCTs) involving 2,226 participants across seven countries. Results showed remote interventions improved medication adherence by 93% and increased sputum conversion rates to 73%. Most participants (84–100%) preferred digital services due to convenience, reduced travel burden, and better communication with healthcare providers. Remote digital health enables flexible, patient-centered care, particularly beneficial in areas with limited healthcare access, while addressing barriers of conventional DOT. However, successful implementation depends on robust technological infrastructure, continuous training for healthcare workers, and patient engagement strategies. Further multicenter studies are needed to validate these findings and guide policy adoption. This review highlights the efficacy and acceptability of remote digital health in TB care, advocating for its integration into treatment programs to enhance compliance and outcomes. Keywords: Remote digital health, pulmonary tuberculosis, medication adherence, health risks, health service